2016
DOI: 10.1090/jag/666
|View full text |Cite
|
Sign up to set email alerts
|

Perverse curves and mirror symmetry

Abstract: This work establishes a subtle connection between mirror symmetry for Calabi-Yau threefolds and that of curves of higher genus. The linking structure is what we call a perverse curve. We show how to obtain such from Calabi-Yau threefolds in the Batyrev mirror construction and prove that their Hodge diamonds are related by the mirror duality.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The SYZ mirror of this configuration was studied by Abouzaid, Auroux, and Katzarkov in [1]. The banana configuration also appears in the Landau-Ginzburg mirror of a genus two curve as studied by Gross, Katzarkov, and Ruddat in [18] and Ruddat in [36]. .…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The SYZ mirror of this configuration was studied by Abouzaid, Auroux, and Katzarkov in [1]. The banana configuration also appears in the Landau-Ginzburg mirror of a genus two curve as studied by Gross, Katzarkov, and Ruddat in [18] and Ruddat in [36]. .…”
mentioning
confidence: 85%
“…Since the arguments of a genus 2 Siegel modular form are coordinates on the moduli space of genus 2 curves (or Abelian surfaces), we expect the complex moduli space of Xban , the mirror of the banana manifold, to contain a subspace isomorphic to the moduli space of genus 2 curves. Indeed, it has already been observed that the mirror of a local banana configuration should be a genus 2 curve [1,18,36].…”
Section: Skoruppa Maassmentioning
confidence: 99%
“…The mirror dual of a curve of genus larger than one is a perverse curve. Mirror dual pairs of perverse curves could also be found inside Calabi-Yau threefolds of Batyrev's construction [Ru13]. Mirror symmetry for non-compact curves has already also been studied by physicists [AAMV05], the perverse curve is then the locus of one-dimensional strata in a toric Calabi-Yau threefold.…”
Section: Introductionmentioning
confidence: 92%